Natural frequency analysis of a light weight box structure / Sahril Kushairi and Kausalyah Venkatason - Kushairi, Sahril; Venkatason, Kausalyah (2005)
Vibration is an important aspect to look at, especially for flexible structure. If two systems for example wing and aileron have the same frequency they will feed energy to each other, this is known as flutter. Flutter is a potentially phenomenon that occurs when an aerodynamics surface goes into resonance with another piece of airframe. This situation could lead to catastrophic situation. Thus the key to eliminate flutter is to prevent either the aileron or the wing from feeding vibratory to the other. It may be done by modifying them so that their natural frequencies are different. Weight saving need to be considered when designing an aircraft. Therefore an aircraft structure including wing must be made light enough for the aircraft to fly. In order to achieve the wing structure are designed so that each part are load bearings. This wing structure is known as light weight box structure. It is basic structure of an aircraft wing. Investigation on static analysis of a wing box structure was done by W. Kuntjoro during the design phase of aircraft structure, structural analysis employing simple equations is used for interim design evaluation. To evaluate the accuracy of simple classical method for structural design of wing panel in particular the associated formulae were used to analyze the response of the outer wing structure due to the static loading. The wing panel stresses due to an applied concentrated loading were calculated by using practical stress analysis methods. Parallel to that, a finite element analysis and a static experiment were performed to evaluate the performance of the employed practical analysis. The main theme of the research to be proposed is the dynamic analysis of light weight box structure. A related research on the vibration characteristic of the wing box structure of a tilt rotor system was done by Branson are examined. The structural analysis and designed in this study are conducted using MSC/NASTRAN finite element code. The analysis is part of the optimization of a composite wing box structure for a civil tilt rotor aircraft. Another research which looked at the development of a finite-element model of a tilt rotor composite wing box with a tip nacelle was conducted by Clements. Results find out that the sensitivity coefficients of torsion natural frequencies with respect to each parameter are shown to be influenced the magnitude of the parameters.